A systematic study of the effect of chemical promotors on the precipitated Fe-based Fischer-Tropsch synthesis catalyst - Hexana, Wonga Mpho (My University, 2009)
In recent years, research interest on improving the catalytic properties of precipitated Febased Fischer-Tropsch synthesis (FTS) catalysts has grown immensely. In particular the effect of promoters on these type of catalysts has attracted much attention. Classical promoters such as copper, potassium and silica are nowadays employed for preparing commercially used FTS catalysts. The promoted catalysts are the catalysts of choice and have been shown to possess chemical properties that improve the catalytic properties of Fe-based Fischer- Tropsch synthesis catalysts. In this thesis we attempted to systematically study effects caused by these promoters as well as the effect of indium as a promoter for Fe. Silica which is often used as a structural promoter and often forms a large portion of the catalyst was added in significantly small amounts and its chemical promotional ability was investigated. It was found that increasing the loading of silica affected the carburization and the reduction properties of the precipitated Fe-based Fischer Tropsch synthesis catalyst. This had an effect on the Fe/Cu and Fe/K2O contacts when the loading was increased. With regard to this study, it was found that silica decreased the activity of the catalyst and shifted the hydrocarbon selectivity to low weight hydrocarbons. All catalysts used in these studies were characterized using N2 physisorption, TPR, DRIFTS, XPS and XRD. Indium was also evaluated as a chemical promoter to a precipitated Fe-based Fischer- Tropsch synthesis catalyst since it is believed that it may induce similar chemical effects as that found for copper. Indeed, it was observed that indium does possess some similar chemical properties to that of copper and also that it affected the precipitated Fe-based Fischer-Tropsch synthesis catalyst in similar ways to copper. It was also instead realized that indium acted as a poorer promoter than Cu for the Fe-based Fischer-Tropsch synthesis catalyst and this was attributed to indium having a low melting point than copper. It was also found that indium acted as a poorer promoter when it was added as a co-promoter to an iron catalyst that contained potassium and silica. It was found that indium lowered the activity of the Fischer-Tropsch synthesis reaction as well as the Water Gas Shift reaction. This was related to a decrease in surface area of the catalyst after the addition of indium. The selectivity was shifted to the production of heavy weight hydrocarbons due to the Fe/K2O contact being promoted. Characterisation techniques such as N2 physisorption, TPR and DRIFTS were employed to elucidate the findings.